English Language Teaching in Saudi Universities and Schools and the Impact of Teaching by Native Speakers and Difference by CELTA Qualified Non-Native Speakers - Hyder, Huma; Anbar, Nashwa Ghazi (Journal of Ecohumanism, 2025)
This research aims to explore how native English-speaking teachers (NESTs) and CELTA-certificated non-native English-speaking teachers (NNESTs) affect ELT practice in Saudi Arabia. Teachers trained in CELTA benefit from practical approaches to teaching, yet the prejudices of native speakerism and cultural misfit approach persevere. It further aims to analyses the advantages of NEST and NNEST alternatives to general shortcomings in the evaluation and recruitment of language teachers and the teaching approaches used.